INFLUENCE OF COMPUTERIZATION ON SCHOOL FAILURES - BUŁKA, Beata (Trends in education, 2008)
The results of questionnaire researches carried among 85 gymnasium pupils from Rybnik are presented. On the base of received results we can ascertain, that computer becomes one of main reasons of school failures.
Keywords: school failures; computer; gymnasium (in Poland - 3 years; type of middle school; starting at age 13/14 and following 6 years of Elementary School. Compulsory for all students. Followed by the non-mandatory 3 years Liceum; 4 years technikum; or 2 or 3 years vocational technical school)